Board Size and Gender Diversity on Boardrooms and Its Impact of Corporate Risk Taking: Evidence from Indonesia - Kusuma Ratnawati (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
The role of company boards as well as it composition in the diversity issues (i.e gender) are very important to make strategic corporate decision. This paper investigates the determinant of corporate risk taking through the size of board and the existence of gender diversity on boardrooms. Focusing on the boards in the non-financial companies, there were 262 companies from period of 2013 to 2016 could be analyzed based on certain criteria. The result of multiple regression analysis showed that the corporate risk taking positively influenced by board size. In contrary, the gender diversity has small negatively effect on corporate risk taking. It suggested that the greater size of the board will increase the volatility of ROA, but the presence of female on boards tends to decrease the volatility of ROA. This paper contributes to the development of theory in the fields of corporate financial management in term of risk taking and lastly. this study also documented that the importance of determining the proportion between male and female boards, as a way to scheming appropriate board composition in company.